Recombinase polymerase amplification with lateral flow strip for detecting Babesia microti infections. (August 2021) - Nie, Zheng; Zhao, Yangnan; Shu, Xiang; Li, Dongfang; Ao, Yangsiqi; Li, Muxiao; Wang, Sen; Cui, Jie; An, Xiaomeng; Zhan, Xueyan; He, Lan; Liu, Qin; et al.
Abstract: Babesia microti is one of the most important pathogens causing humans and rodents babesiosis—an emerging tick-borne disease that occurs worldwide. At present, the gold standard for the detection of Babesia is the microscopic examination of blood smears, but this diagnostic test has several limitations. The recombinase polymerase amplification with lateral flow (LF-RPA) assay targeting the mitochondrial cytochrome oxidase subunit I ( cox I) gene of B. microti was developed in this study. The LF-RPA can be performed within 10–30 min, at a wide range of temperatures between 25 and 45 °C, which is much faster and easier to perform than conventional PCR. The results showed that the LF-RAP can detect 0.25 parasites/μl blood, which is 40 times more sensitive than the conventional PCR based on the V4 variable region of 18S rRNA. Specificity assay showed no cross-reactions with DNAs of related apicomplexan parasites and their host. The applicability of the LF-RPA method was further evaluated using two clinical human samples and six experimental mice samples, with seven samples were positively detected, while only three of them were defined as positive by conventional PCR. These results present the developed LF-RPA as a new simple, specific, sensitive, rapid and convenient method for diagnosing infection with B. microti . This novel assay was the potential to be used in field applications and large-scale sample screening.